2011
DOI: 10.1557/opl.2011.1512
|View full text |Cite
|
Sign up to set email alerts
|

MD Simulations of Compression of Nanoscale Iron Pillars

Abstract: It is now possible to create perfect crystal nanowires of many metals. The deformation of such objects requires a good understanding of the processes involved in plasticity at the nanoscale. Isotropic compression of such nanometre scale micropillars is a good model system to understand the plasticity. Here we investigate these phenomena using Molecular Dynamics (MD) simulations of nanometre scale single crystal BCC iron pillars in compression.We find that pillars with large length to width ratio may buckle und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Most molecular dynamic and dislocation dynamic modelling of bcc micropillars has concentrated on molybdenum and has indicated that dislocations can undergo complex reactions leading to size effects [37,38]. Recent MD modelling of iron micropillars has shown the formation of localised slip bands very similar to those seen here in the unimplanted pillars [39].…”
Section: Resultssupporting
confidence: 61%
“…Most molecular dynamic and dislocation dynamic modelling of bcc micropillars has concentrated on molybdenum and has indicated that dislocations can undergo complex reactions leading to size effects [37,38]. Recent MD modelling of iron micropillars has shown the formation of localised slip bands very similar to those seen here in the unimplanted pillars [39].…”
Section: Resultssupporting
confidence: 61%